2004
DOI: 10.1158/0008-5472.can-04-2202
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Drug Ellipticine Forms Covalent DNA Adducts, Mediated by Human Cytochromes P450, through Metabolism to 13-Hydroxyellipticine and EllipticineN2-Oxide

Abstract: Ellipticine is an antineoplastic agent, the mode of action of which is considered to be based on DNA intercalation and inhibition of topoisomerase II. We found that ellipticine also forms the cytochrome P450 (CYP)-mediated covalent DNA adducts. We now identified the ellipticine metabolites formed by human CYPs and elucidated the metabolites responsible for DNA binding. The 7-hydroxyellipticine, 9-hydroxyellipticine, 12-hydroxyellipticine, 13-hydroxyellipticine, and ellipticine N 2 -oxide are generated by hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
235
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(252 citation statements)
references
References 24 publications
17
235
0
Order By: Relevance
“…Structural data as well as studies on drug analogues are readily available. [74,75] We will probe the versatility of the linearizing scheme for controlling ellipticine-derivatives/DNA binding, isolated in gas phase and with fixed geometry. [76] Clearly, for the eventual control of ligand binding, the property of interest is not the potential energy of interaction but rather the free energies of binding: solvation or entropic contributions can be crucial, as is well known in general, [77] and in the particular case of ellipticine.…”
Section: Control Of Ligand Bindingmentioning
confidence: 99%
“…Structural data as well as studies on drug analogues are readily available. [74,75] We will probe the versatility of the linearizing scheme for controlling ellipticine-derivatives/DNA binding, isolated in gas phase and with fixed geometry. [76] Clearly, for the eventual control of ligand binding, the property of interest is not the potential energy of interaction but rather the free energies of binding: solvation or entropic contributions can be crucial, as is well known in general, [77] and in the particular case of ellipticine.…”
Section: Control Of Ligand Bindingmentioning
confidence: 99%
“…Previous molecular studies suggested that ellipticine acted primarily through its binding to nucleic acids and inhibition of topoisomerase II (topo II) and topo II -mediated DNA damage (14). Cytochrome P450-dependent oxidation at the 7-or 9-carbon position has been shown to promote DNA intercalation and adduct formation, thereby enhancing the cytotoxic potential of these agents (15). Additionally, selection for ellipticine resistance in a Chinese hamster lung cell line resulted in a phenotype that was cross-resistant to all known topoisomerase-targeting agents as well as several additional P-glycoprotein substrates (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In experiments, aromatic N-oxides formed by CYPs have been found for a large number of compounds, primarily with pyridine, [104][105][106][107][108][109] pyrimidine, 110 and quinoline fragments. 111 However, no N-oxides of nitrogen atoms in five-membered aromatic rings have been found.…”
Section: Oxidations Of Tertiary Amine Nitrogen Atomsmentioning
confidence: 99%